Job Design and Organizational Culture as Drivers of Innovation: The Role of Job Satisfaction at the Indonesian Aviation Academy Banyuwangi - Diah Utami Rahayu; Ika Barokah Suryaningsih; Etty Puji Lestari (International Journal of Economics Development Research (IJEDR), 2024)
This study investigates the impact of job design, organizational culture, and job satisfaction on innovative behavior at the Indonesian Aviation Academy Banyuwangi. Using statistical analysis and SEM-PLS, we examined direct and indirect relationships between these variables. The results indicate that both job design and organizational culture have significant positive effects on innovative behavior. A well-structured job design enhances employees' involvement and responsibility, which in turn boosts innovative behavior. Likewise, a strong organizational culture fosters an environment where innovation is valued and promoted. Job satisfaction also positively influences innovative behavior; however, it does not mediate the relationship between job design and innovative behavior or between organizational culture and innovative behavior. Consequently, while job satisfaction contributes to innovative behavior, it does not act as a mediator in these relationships. The findings suggest that for API Banyuwangi, focusing on comprehensive job designs and a supportive organizational culture is crucial for fostering innovation, with job satisfaction playing a supportive role rather than a mediating one.